p(x) * r(x) = ab^x * cd^x
p(x) * r(x) = (a*c)*(b^x*d^x)
p(x)*r(x) = ac(bd)^x
For the last step, I used the rule that (ab)^x = a^x*b^x
<h3>Final Answer: ac(bd)^x</h3>
Answer:
the awnser is B
Step-by-step explanation:
the awnser is B
Answer:
x=10, y=4
Step-by-step explanation:
3x-3y=18
(-)3x-(-)8y=-(-)2 -3x+8y=2 add to first equation to eliminate x
5y=20
y=4
substitute y with 4
3x-3(4)=18
3x=30
x=10
x=10,y=4
70+75+80+90+100=415
415/5=83
<span>After the lowest grade is dropped, Janet's average would be an 83%</span>
ANSWER
![(3x - 2)(x + 4)](https://tex.z-dn.net/?f=%283x%20%20-%202%29%28x%20%2B%204%29)
EXPLANATION
The given quadratic trinomial is
![3 {x}^{2} + 10x - 8](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%20%2B%2010x%20-%208)
Comparing to the general quadratic trinomial:
![a{x}^{2} + bx + c](https://tex.z-dn.net/?f=a%7Bx%7D%5E%7B2%7D%20%20%2B%20bx%20%20%2B%20c)
We have a=1, b=10 and c=-8
![ac = 3 \times - 8 = - 24](https://tex.z-dn.net/?f=ac%20%3D%20%203%20%20%5Ctimes%20%20-%208%20%3D%20-%2024)
The factors of -24 that adds up to 10 are -2 and 12.
We split the middle term to obtain;
![3 {x}^{2} + 12x - 2x- 8](https://tex.z-dn.net/?f=3%20%7Bx%7D%5E%7B2%7D%20%20%20%2B%2012x%20%20%20-%202x-%208)
Factor;
![3x(x+ 4) - 2(x + 4)](https://tex.z-dn.net/?f=3x%28x%2B%204%29%20%20-%20%202%28x%20%2B%204%29)
Factor further;
![(3x - 2)(x + 4)](https://tex.z-dn.net/?f=%283x%20%20-%202%29%28x%20%2B%204%29)
The last option is correct.